1995
DOI: 10.1046/j.1365-313x.1995.07060877.x
|View full text |Cite
|
Sign up to set email alerts
|

Two of three promoter elements identified in a rice gene for proliferating cell nuclear antigen are essential for meristematic tissue‐specific expression

Abstract: Proliferating cell nuclear antigen (PCNA) is an auxiliary protein of DNA polymerase delta, and it is highly conserved among eukaryotes. The rice PCNA promoter, truncated to position -263, was previously shown to confer meristematic tissue-specific expression in transgenic plants. By DNasel footprinting and gel retardation analysis, three cis-acting elements were defined in this truncated promoter, which designated site I (-201 to -194, CCAGGTGG), site IIa (-197 to -188, TGGGCCCGT) and site IIb (-178 to -169, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 0 publications
5
80
0
Order By: Relevance
“…This suggests that sites Ila and Ilb most probably function as positive cisacting elements in proliferating cells. In addition, results of electrophoretic mobility shift assays (EMSAs) have also shown that these sites bind to nuclear proteins with identical or similar DNA binding specificity in rice and tobacco (Kosugi et al, 1995). These data suggest that sites Ila and Ilb have a similar function in diversified species.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…This suggests that sites Ila and Ilb most probably function as positive cisacting elements in proliferating cells. In addition, results of electrophoretic mobility shift assays (EMSAs) have also shown that these sites bind to nuclear proteins with identical or similar DNA binding specificity in rice and tobacco (Kosugi et al, 1995). These data suggest that sites Ila and Ilb have a similar function in diversified species.…”
Section: Introductionmentioning
confidence: 86%
“…We have previously defined the promoter elements (site Ila and site llb) essential for meristematic tissue-specific expression of the rice PCNA gene (Kosugi et al, 1995). In this study, we isolated cDNAs for specific binding proteins for sites Ila and Ilb.…”
Section: Cloning Of the Pcfl And Pcf2 Cdnasmentioning
confidence: 99%
See 2 more Smart Citations
“…Two families of proteins that bind to the CRT in promoters of genes responding to these stresses are C repeat binding factors (CBFs; also known as DRE binding factor 1s [DREB1s]) and DREB2s (Jaglo-Ottosen et al, 1998;Liu et al, 1998). The sequence AGGCCCAT ( Figure 2D) contains the core of a sequence originally described as one of three cis-acting elements in the promoter of the proliferating cell nuclear antigen (PNCA) gene, originally in rice (Oryza sativa), which was thus designated Site IIa (Kosugi et al, 1995). Rice proteins identified as binding to this motif include bHLH transcription factors PCF1 and PCF2 (Kosugi and Ohashi, 1997).…”
Section: Imposed [Ca 2+ ] C Elevations Are Capable Of Inducing Signifmentioning
confidence: 99%